Defect engineering via the F-doping of β-MnO2 cathode to design hierarchical spheres of interlaced nanosheets for superior high-rate aqueous zinc ion batteries. Issue 32 (17th June 2021) - Kim, Seoyeong; Koo, Bon-Ryul; Jo, Yong-Ryun; An, Ha-Rim; Lee, Young-Geun; Huang, Chun; An, Geon-Hyoung
Abstract : The valance engineering of β-MnO2 via F-doping process triggers designing hierarchical spheres with interlaced nanosheets to accelerate electrochemical kinetics and capacity, ensuring superior high-rate aqueous zinc ion battery performances. Abstract : The rechargeable aqueous Zn ion battery (ZIB) is a promising candidate for next-generation energy storage technology due to its low cost, low flammability, inherent safety, and high theoretical capacity. Nevertheless, the β-MnO2 cathode material continues to be limited by inactive ion insertion and transport kinetics due to a relatively narrow tunneling pathway, thus leading to low capacity and rate capabilities. Hence, to achieve a high-performance ZIB, the presence of lattice and defect structures in the β-MnO2 is required to promote the electrochemical reactions. Herein, for the first time, a β-MnO2 cathode with a hierarchical structure consisting of spheres of interlaced nanosheets is introduced via efficient defect engineering using fluorine (F)-doping and oxygen vacancies, thus leading to improved ion insertion and transport kinetics along with an enhanced electrical conductivity. The ZIB is shown to exhibit a high energy density (288 W h kg −1 at a power density of 90 W kg −1 ), a superior high-rate performance (energy density of 158 W h kg −1 at a power density of 1800 W kg −1 ), and a capacity retention (85% after up to 150 cycles). These results highlight the potential of defect-engineered cathode materials for the enhanced electrochemical performance of rechargeable aqueous batteries.